Effective modes of operation of radio-bombing devices for covert information gathering in the field of noise interference - Serhiienko , S.P.; Krizhanovski, V.G.; Chernov, D.V.; Zahoruiko , L.V. (Radiotekhnika, 2021)
The information security of modern society is in constant counteraction and constant improvement of technical means used for unauthorized information pickup, and technical means that prevent it. The paper analyzes examples of methods of applying noise interference to counteract the unauthorized pickup. The possibility of unauthorized pickup by passive radio devices using noise interferences is shown and analyzed using noise interferences, which are used to suppress the eavesdropping devices. The transfer of picked up information is possible both by radio wave and low-frequency channels using metal structures or water pipes. As a model of noise interference, a random narrow-band signal with a Gaussian distribution was used. The electrical model of the device was simulated by a transmission line with a high-frequency diode at its end. The idealized exponential dependence of the diode current on the voltage was used. The reflected wave spectra are obtained for different ratios of the transmission line resistance, the differential resistance of diode, and the external offset voltage at the diode. The modes and features of analog and digital information transmission by the radio tab device using energy of radio noises are analyzed. In the radio tab device, the information is transmitted by reflected wave, the spectrum of which is distorted at a nonlinear element placed at the end of transmission line. An analysis of the device operation was carried out along the full possible frequency range associated with the spectrum of the incident noise interference. The optimal elements parameters for the passive electrical circuit are calculated: the resistance of the transmission line, the differential resistance of the diode, the offset voltage, and the modulation mode, depending on the frequency range in which the leak is possible.